To Assess the Functional Outcome of AO/ASIF A3 Distal Femoral Fractures Fixed by Contour Locking Plate as Fixator Internee (Medical Forum Monthly, 2020)
Objective: To evaluate the radiological and functional outcome of Association for Osteosynthesis (AO)/ Association for study of Internal Fixation (ASIF) A3 of distal femoral fractures treated with contour locking plates as fixator internee.Study Design: Descriptive case series study.Place and Duration of Study: This study was conducted at the Mayo hospital Lahore from February 2018 to August 2019.Materials and Methods: Patients with close intra articular commutated distal femoral fractures are admitted and operated with distal femoral contour locking plates by fixator internee principle. Follow up visit were planned as, after 4tHweek, 6thweek and then monthly for 08 months. Radiological union was noted and functional evaluation was done by using the modified Mize outcome criteria and which was graded 1 as excellent, 2 as good, 3 as fair and 4 as failure.Results: 16 patients with mean age 40.43 years of age were operated. Male patients were 10 (62.5%) while female were 6(37.5%). Patients were assessed with modified Mize criteria and excellent in 7 (43.75%), good in 4, (25%), Fair in 3(18.7%) and failure in 2, (12.5%) patients. No implants failure was noted .NO nonunion was noted. Bone grafting (bone marrow aspiration) was done in 5 cases.Conclusion: When locking plate is applied as fixator internee, in intra articular comminuted fractures showed an excellent and good results radiological and functional results in AO/ASIFA3 complicated fractures in majority of the patients.